PENGARUH NPL, LIKUIDITAS, DAN RENTABILITAS TERHADAP CAR PADA BPR KONVENSIONAL SKALA NASIONAL DI INDONESIA - Putri, Ni Putu Sinta Wira; Dana, I Made (E-Jurnal Manajemen, 2018)
This study was conducted to analyze the effect of non-performing loans (NPL), Loan to Deposit Ratio (LDR), Return on Equity (ROE) and Return on Assets (ROA)of the Capital Adequacy Ratio (CAR) partially on a national scale Conventional BPR in Indonesia during the period November 2014 - 2016. The data collection method used is a non-participant observation. Sources of data in this research is secondary data that is accessed on the official website of Bank Indonesia (BI). The data analysis technique used is multiple linear regression were processed with SPSS program with census sampling technique. This study found that the results of NPL and ROA have significant positive effect on CAR. LDR have positive but not significant effect on CAR and ROE have significant negative effect on CAR.